Into the Wilderness : The Lewis and Clark Expedition - Holmberg, James J. (James John), 1958- (Book collections on Project MUSE., 2003)
""When Thomas Jefferson sent a team of explorers to discover a way to the Pacific Ocean two hundred years ago, the western border of the United States was the Mississippi River. It was Jefferson's dream to uncover the mysteries of the distant lands beyond. In 1803, the president sent a team of thirty men, lead by Meriwether Lewis and William Clark, up the Missouri River, across the Rocky Mountains, down the Columbia River to the Pacific, and back home again. During this monumental, two-and-a-half-year expedition, Lewis and Clark gathered samples of plants, animals, and Indian crafts. Into t